Colégio Nossa Senhora de Lourdes, Farroupilha/RS : histórias de sujeitos e práticas (1922-1954) - Belusso, Gisele (My University, 2016)
This study intended to understand the historic process of Nossa Senhora de Lourdes School, located in Farroupilha/RS, to broad knowledge about Brazilian and gaúcha history of education. The research was done based on school cultures of the Institution, subjects, and practices in Primary Education as categories of analysis. The institution, founded in 1917, belongs to Education Association São Carlos of Missionary Scalabrinian Sisters of São Carlos Borromeo of Italian origin. The timeline used in this study is 1922, when the first address move of the institution occurs, until 1954, when the functioning of secondary course (curso ginasial) is authorized to function. Theoretical-methodological presuppositions of Cultural History directed the analysis, mainly with the contribution of historians such as Burke (1992, 2000), Le Goff (1996), Chartier (2002), and Pesavento (2008). To base the understanding of school cultures, contributors are Julia(2001), Viñao Frago and Escolano (2001), Vidal (2005;2009), and Faria Filho (2007). The main sources of information for research are: (a) written documents (Book of Sagrado Coração de Jesus Parish, minute books, school final exams and registers of apostolic life of five religious-teachers), (b) photographs, and (c) oral history of seven subjects linked to the school (five ex-students and two ex-religious-teachers). Nevertheless, other sources were used in the course of the narrative elaboration, as, for example, the Report of Previous Verification for authorization of “ginásio” course, newspapers and documents of personal collections of interviewees. The narrative done allowed to understand the emergence of the school in the local context, as well as the emergence of the Missionary Scalabrinian Sisters of São Carlos Borromeo Congregation, its action in the education área and its expansion to Rio Grande do Sul. Related to school subjects, students, teachers and directors, it was possible to note that students bring with them some traces of ethnicity and culture which are characteristic of this place. The teaching staff is mainly formed by religious-teachers which education is firstly religious. Professional education was made possible by the congregation in different forms (complementary school, music courses, dactylography, among others). Directors, congregation sisters, were initially not from the region, but this has changed a long time. The post of manager represents a function, which is not exclusive and is apparently linked to other hierarchies in the congregation. School practices, analyzed from traces and representations, allowed noting (a) the classroom as a privileged space for school practices, (b) reading and writing practices as a common thread of the other knowledge sets, (c) permeated by discipline, order and religiosity, and (d) forms of quantifying learning. These practices, hybridized by “New School” ideas, by educational laws, and by the process of nationalization marked school cultures of the researched school.
A pesquisa buscou compreender o processo histórico do Colégio Nossa Senhora de Lourdes, localizado em Farroupilha/RS, a fim de ampliar o conhecimento sobre a história da educação gaúcha e nacional. A investigação teve como categorias de análise as culturas escolares da instituição, os sujeitos e práticas no Ensino Primário. A instituição, fundada em 1917, pertence à Associação Educadora São Carlos das Irmãs Missionárias de São Carlos Borromeo Scalabrinianas de proveniência italiana. O recorte temporal do estudo é de 1922, ano em que ocorre a primeira mudança de endereço da instituição, até 1954, quando é autorizado o funcionamento do curso ginasial. Os pressupostos teórico-metodológicos da História Cultural orientaram a análise, sobretudo com as contribuições dos historiadores Burke (1992, 2000), Le Goff (1996), Chartier (2002) e Pesavento (2008). Já para ancorar a compreensão das culturas escolares, contribuem Julia (2001), Viñao Frago e Escolano (2001), Vidal (2005, 2009) e Faria Filho (2007). Os principais documentos da investigação são: (a) documentos escritos (Livro Tombo da Paróquia Sagrado Coração de Jesus, livros de atas, exames finais do colégio e registros da vida apostólica de cinco professoras-religiosas), (b) fotografias e (c) história oral de sete sujeitos vinculados à instituição escolar (cinco ex-alunos e duas ex-professoras-religiosas). Porém, outras fontes foram utilizadas no decorrer da elaboração da narrativa como, por exemplo, o Relatório de Verificação Prévia para autorização do ginásio, jornais e documentos de acervos pessoais dos entrevistados. A narrativa realizada permitiu compreender o surgimento da instituição escolar no contexto local, bem como a emergência da Congregação das Irmãs Missionárias de São Carlos Borromeo Scalabrinianas, sua atuação no campo educacional e a expansão para o Rio Grande do Sul. Com relação aos sujeitos escolares, discentes, docentes e diretoras, foi possível perceber que os alunos trazem consigo marcas de etnicidade e cultura próprias deste local. O corpo docente, por sua vez, caracteriza-se por ser formado, principalmente por professoras-religiosas que têm como formação inicial a religiosa. Já a formação profissional, ela foi oportunizada pela congregação de diferentes formas (escola complementar, cursos de música, datilografia, dentre outros). As diretoras, irmãs da congregação, inicialmente não eram da região, mas essa realidade foi alterando-se com o passar do tempo. O cargo de diretora representa uma função que não é exclusiva e está aparentemente vinculada a outras hierarquias na congregação. As práticas escolares, analisadas a partir dos indícios e representações, permitiu perceber (a) a sala de aula como espaço privilegiado das práticas escolares, (b) as práticas de leitura e de escrita, como um fio condutor dos demais saberes, (c) permeados pela disciplina, ordem e religiosidade, e também (d) as formas de quantificar a aprendizagem. Tais práticas hibridizadas pelas ideias escolanovistas, legislações educacionais e pelo processo de nacionalização marcaram as culturas escolares da instituição pesquisada.
Keywords: Colégio Nossa Senhora de Lourdes - História; Escolas religiosas; Escolas - Farroupilha (RS) - História; Colégio Nossa Senhora de Lourdes - History; Church schools; Schools - Farroupilha (Brazil) - History